Pelatihan Pembuatan Tempe Daun Singkong Sebagai Cemilan Bernutrisi Untuk Ibu Hamil Dan Anak-Anak Sebagai Pencegahan Stunting Di Kota Padang Panjang - relin yesika; Yahdian Rasyadi; , Amri Bakhtiar; Nanda Rahma Desra; Antisa Larasari Deflorian; Ardilla Marisya (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Prevention of stunting in toddlers can be done starting during pregnancy. Nutritional intake in pregnant women can be done by consuming quality food. In an effort to fulfill nutrition for pregnant women and children by consuming nutritious snacks, this service conducted training on making cassava leaf tempeh to mothers in the Bukit Surungan village, West Padang Panjang, Padang Panjang City on July 29, 2022. The training activity began with an explanation of the content of cassava leaf tempeh and how to make cassava leaf tempeh. Next, there was a demonstration of how to make tempeh from cassava leaves and the processing of cassava leaf tempeh that had been prepared previously into fried cassava leaf tempeh. The training participants said they liked cassava leaf tempeh and were interested in processing cassava leaves into tempeh to get additional food with high nutritional value for pregnant women, toddlers and children.